2016
DOI: 10.1042/cs20150685
|View full text |Cite
|
Sign up to set email alerts
|

Infant adiposity at birth and early postnatal weight gain predict increased aortic intima-media thickness at 6 weeks of age: a population-derived cohort study

Abstract: Infant body composition and postnatal weight gain have been implicated in the development of adult obesity and cardiovascular disease, but there are limited prospective data regarding the association between infant adiposity, postnatal growth and early cardiovascular parameters. Increased aortic intima-media thickness (aortic IMT) is an intermediate phenotype of early atherosclerosis. The aim of the present study was to investigate the relationship between weight and adiposity at birth, postnatal growth and ao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 58 publications
2
13
1
Order By: Relevance
“…Also Rathsman et al [15] reported increased cIMT in diabetic adolescents with positive correlation between cIMT and waist circumference [15]. Similarly McCloskey et al [17] concluded that increased infant weight and adiposity at birth, as well as increased early weight gain, were positively associated with aortic intima-media thickness. In the current study, increased aIMT had significant correlation with age of the patients (P = 0.0001) but not correlated to other cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also Rathsman et al [15] reported increased cIMT in diabetic adolescents with positive correlation between cIMT and waist circumference [15]. Similarly McCloskey et al [17] concluded that increased infant weight and adiposity at birth, as well as increased early weight gain, were positively associated with aortic intima-media thickness. In the current study, increased aIMT had significant correlation with age of the patients (P = 0.0001) but not correlated to other cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Serum total cholesterol was determined by a commercial kit (Boehringer-Mannheim, Mannheim, Germany) [16]. High-density lipoprotein (HDL) cholesterol was separated from the serum by precipitation of the other lipoproteins with a heparin/manganese procedure [17]. Low-density lipoprotein (LDL) cholesterol was calculated using the Friedewald equation.…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of obesity in children and adolescents has increased in recent years, reaching 17% in the United States (Ogden et al, 2015; Skinner et al, 2018). Overweight in early ages is highly related to obesity at adulthood (McCloskey et al, 2016; Araujo de Franca et al, 2016; Prioreschi et al, 2018; Stettler et al, 2005), besides increased cardiovascular disease risk appears at pediatric age (Genovesi et al, 2010; Ayer et al, 2015). In rodents, the reduction of litter size during suckling, firstly demonstrated by Kennedy (1957), has been used to study postnatal excessive weight gain due to the enhanced milk intake caused by greater availability, as well as increased milk fat concentration about 7 days after litter reduction (Sefcikova and Racek, 2015; Mozes et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The S4SFT is identified as a good predictor of the changes in the fat mass during the first year of life and measures are required for younger children. 7,8 S4SFT within the first few months of life has been associated with cardiovascular health risk with an increase of aortic intima media thickness at 6 weeks 9 and obesity risk at 6 years of age (OR 1.61, 95% CI 1.09, 2.38). 10 Measurement of SFT has several requirements for successful implementation that include a standard protocol, adequate training of the measurement techniques to avoid observer variability 11 (because it takes longer than standard anthropometry to complete) and translation of S4FT into an estimated total body fat mass for Asian children.…”
Section: Challenges In Measuring Body Composition In Early Lifementioning
confidence: 99%